The Concept of Education Based on Exemplary To the Prophet Muhammad PBUH: Perspective Muhammad Ibn Abdul Wahab - Ainul Haris (Universitas Muhammadiyah Malang, 2021)
This study examines the concept of education in the perspective of Muhammad Ibn’ Abd al-Wahhāb, which is based on his exemplary to the Prophet Muhammad Sallallahu’ alaihi wa Sallam. The da’wah of Ibn’ Abd al-Wahhāb raises the pros and cons among Muslims. The issue of education and exemplary is fundamental in Islam, because for a Muslim, the Prophet Muhammad Sallallahu’ alaihi wa Sallam is the first figure to be followed by his words, carried out his orders and decisions and his behaviour imitated or emulated. This research answers how the concept of education, according to Shaykh Muhammad bin ‘Abdul Wahhāb which is taken from the figure of the Prophet Sallallahu’ alaihi wa Sallam. The type of research that the writer uses is library research which specifically examines a problem to obtain data in this study’s writing. Sources of data in this study were obtained from primary data and secondary data. The primary sources in this writing are the original works or writings of Shaykh Muhammad bin ‘Abdul Wahha>b. The secondary sources in this study are educational books, journals of morality aqidah in Islam that are relevant to the research discussion. The approach used in this research is historical-philosophical. The data obtained were then analysed by content analysis (content analysis). This research resulted in understanding the concept of Shaykh Muhammad bin ‘Abdul Wahhāb about education that is in accordance with the salaf manhaj, namely ittiba’ ‘(imitating) the Prophet and based on al-Qur’a>n and Hadith. This study also explains that Shaykh Ibn’ Abd al-Wahhāb carries out and teaches the concept of education in accordance with the teachings of the Prophet Sallallahu’ alaihi wa Sallam. The method of delivering da’wah, thoughts and examples of the behaviour of Shaykh Muhammad bin ‘Abdul Wahha>b is based on exemplary education to the Prophet with all its purity without subtracting or any addition out from it, as well as staying away from all prohibitions in the form of bid’ah, khurafat and things that deviate from Islamic teachings.",